Recovery after disaster : lessons learned from Islamic Studies Library's experiences - Juhaida, A.R. (2014)
After landslides struck the Islamic Studies Library, University of Malaya on 20th October 2008, now, the library has started its services as usual at the same building and at the same location as before the landslides. The main purpose of this paper is to share the library's experience on recovering the library's collection, planning the relocation of library and designing the new outlook for the library. The paper also discusses on the need of having a proper disaster management plan for a library as a guideline for efficiently action taken if any disaster occurred in the future.